Peta Perdebatan Akademik dalam Kajian Hadis - Abdul Hakim Wahid (Refleksi, 2019)
Knowing the map of studies in science fieldwill make easier for researchers to conduct further studies. Therefore, in every scientific work, a literature study is required, because it can describe the academic debates between scholars on a theory, including in the hadith studies. This paper deals to map out the theories discovered by the orientalists and the rebuttal of scholars, systematically. The results of this study can be used by students of Islamic studies of hadith concentrationas a theoretical framework and as a reference in coursesof Western studies on the hadith.